The Role of Organizational Commitment in Mediating the Relationship Between the Leadership Serves "Diuwongke" to the Citizen Organizational Behavior of Employees Working in the Service Field of Cirebon Region 3 - Tika Trinuryana; Vina Rahmania; Sandi Nasrudin Wibowo (Indonesian Journal of Business Analytics, 2024)
The main objective of this research is to determine whether organizational commitment has a mediating role in the relationship between servant leadership "diuwongke" and organizational citizenship behavior. Path analysis techniques were used to analyze the data collected. This research reveals that servant leadership "diuwongke" has a significant effect on organizational citizenship behavior which is mediated by organizational commitment, and organizational commitment has a direct impact on organizational citizenship behavior. This study also points out several limitations as well as future research directions.